Nusyuz dalam Hukum Islam: Bias Gender antara Perempuan dan Laki-Laki - Andi Syahrani Afdhal; Meli Kamelia; Gita Maharani; Kurniati Kurniati (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2026)
This study discusses the concept of nusyûz in Islamic law, the differences in its treatment between husband and wife, and efforts to reinterpret it for greater justice in the household. Traditionally, nusyûz is only associated with wife's disobedience, while husband's negligent behavior is rarely considered nusyûz, which is influenced by classical interpretations and patriarchal culture. This research approach is qualitative descriptive with literature study, using data sources in the form of the Qur'an, classical and contemporary fiqh literature, and positive legal regulations such as the Compilation of Islamic Law and the Marriage Law. The results show that nusyûz should be understood as a reciprocal responsibility between husband and wife, not a tool of control over women. Reinterpretation based on gender equality, maqāṣ id sharia, and the principle of justice can encourage the creation of harmonious families, mutual respect, and freedom from gender-based violence. This study provides recommendations for making family law regulations and practices more just, balanced, and in accordance with universal Islamic values.